Granulomatous lesions and Mycobacterium avium subsp. paratuberculosis in portuguese wild boars (Sus scrofa) - Matos, A.C. (2016)
Granulomatous lesions and Mycobacterium avium subsp. paratuberculosis in portuguese wild boars (Sus scrofa).